Harvest age data for GIFT tilapia G20 (2024) TiLV resistant individuals - Mahmuddin, Mahirah; Izadi, Fariba; Hamilton, Matthew (2025)
2312 different GIFT Tilapia harvest age data is populated in this file. The demographic information includes the depth, standard length, total length and total weight of the individual fish.